PARAMETER EVALUASI MANAJEMEN PERAWATAN BANGUNAN GEDUNG PENDIDIKAN DI PERGURUAN TINGGI NEGERI - Rahmannullah, Fauzi (-)
Treatment of Building represent important shares from system of building which is often forgotten, we tend to own ability to build but skillful insuf`ficient in looking after and take care of it, so that a lot of infrastructure in various place seen to destroy and do not maintain better. In this research is selected by University of Indonesia Education ( UPI), University Pedjajaran, and Bandung the Technological Institute as sampel research, and in general assist preparation of College of Country face independence become Legal Body Publik Ownwrship ( BHMN). Method of Research weared by descriptive. Than this research yield information of management of treatment of building of building in PTN in Town of Bandung and obtain get parameter evaluate management of treatment of building in College of Country and also the parameter evaluate standard of work of building treatment. Mount quality of management of treatment of building of education in three PTN in Bandung pertained enough come near less, and really still look for format system of best treatment, now still a lot of feebleness that happened. Parameter Evaluate Management of treatment of building of building yielded cover aspect : Treatment Planning, Organisasai Treatment, Treatment Execution, Treatment Operation, Treatment Budget, Treatment Personnel. Result of this research give very useful input to : architect, organizer of treatment of building unit, governmental. and specially for of Head of PTN have to be more care in determining the best policy about building treatment